2004
DOI: 10.1111/j.1740-8261.2004.04027.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral waveform analysis of major arteries in conscious dogs by Doppler ultrasonography

Abstract: Normal values of arterial blood flow velocity and waveforms in major arteries of 10 healthy conscious Beagle dogs were determined using Doppler ultrasonography. Peak systolic, early diastolic, and end-diastolic velocities of the basilar artery, common carotid artery, abdominal aorta, external iliac artery, femoral artery, and peak ejection velocity of the valvular aorta were evaluated. Pulsatility index (PI) of the basilar artery and blood pressure were recorded. All arteries had a high-resistance flow pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
2
23
1
4
Order By: Relevance
“…In this study the diagram of Doppler spectra of the blood flow in the common femoral artery obtained in young and old conscious healthy dogs was triphasic. This result agrees with those reported for large high-resistance arteries in different ages (Fernández del Palacio et al 2003;Lee et al 2004;Nogueira et al 2005).…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In this study the diagram of Doppler spectra of the blood flow in the common femoral artery obtained in young and old conscious healthy dogs was triphasic. This result agrees with those reported for large high-resistance arteries in different ages (Fernández del Palacio et al 2003;Lee et al 2004;Nogueira et al 2005).…”
Section: Discussionsupporting
confidence: 95%
“…It has been determined that the true velocity-values of the blood flow in the femoral artery can only be obtained, if the Doppler angle does not exceed 60 0 (Solomon et al 1995;Szatmári et al 2001;Fernández del Palacio et al 2003;Lee et al 2004;Nogueira et al 2005). The Doppler velocities were not significantly different in the present study, although their mean values have been lower in old healthy dogs.…”
Section: Discussionmentioning
confidence: 98%
“…In 2004, Lee et al observed an average systolic peak velocity of 115 ± 17 cm/s and an average final diastolic velocity of 39 ± 7 cm/s in the common carotid artery of 1-year-old beagles. They observed that the caudal velocity was generally higher than the cranial velocity [9,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Doppler ultrasound has become an accepted and routine method for the investigation of blood haemodynamics in both humans and animals since it can rapidly and non-invasively provide information regarding many vascular diseases (Lee et al 2004). The technique provides dynamic real-time anatomical vascular information; moreover, it allows for the detection of the presence, direction, and type of blood flow into a vessel (Szatmari et al 2001).…”
mentioning
confidence: 99%